Rancang Bangun Strategi Pemberdayaan UMKM melalui Wakaf Produktif Berbasis Model Sharia Grameen Bank di Era New Normal - Abd. Wahab; Siti Masfufa; Ridan Muhtadi; Nur Rachmat Arifin (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2022)
Abstract Economic conditions in the midst of the Covid-19 pandemic, the people of Bira Tengah Village, Sampang Regency, have not been able to achieve a level of welfare even though in the village there is tourism potential for Lon Malang Beach and abundant marine products. The majority of housewives in the area do not have income-generating jobs. Thus, a solution is needed to optimize the role of housewives in the village to improve their economy in this new normal era. The purpose of this research is to create a solution idea in revitalizing the community's economy in order to alleviate poverty and increase the role of housewives in Central Bira in the new normal era. In writing this scientific paper, it uses research methods with a qualitative descriptive approach, data collection by interviews and literature studies as data sources. The concept of Sharia Grameen Bank is a model of Islamic microfinance institutions that apply sharia economic principles by utilizing capital from cash waqf and partnering with cooperatives supported by the use of the LOL website (Lon Malang Luminous Heaven) which can optimize the implementation process of Sharia Grameen Bank implementation). LOL (Lon Malang Luminous Heaven) is a website that is used as a medium in raising and distributing funds from productive waqf empowerment programs through cooperatives with murabahah contracts to housewives business groups in Central Bira.